eBuyer, beware. - Cherry, S. (IEEE spectrum)
There are some great bargains on eBay. As well there ought to be-after all, there's also great risk. When you're buying at a virtual yard sale where you can't see the merchandise or from a distant retailer you've never heard of, there's a fear that the goods won't be shipped or that even if they are, that they'll be defective in some way. If only you could get the bargain without the worry! Perhaps you can. A company called buySafe Inc. in Alexandria, Va., has come up with a way to use an ancient financial instrument, known as a surety bond, to remove the uncertainty from eBay transactions.